2018
DOI: 10.1177/1203475418761859
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Moderate to Severe Atopic Dermatitis in Canadian Children: A Cross-Sectional Survey

Abstract: This survey demonstrates the medical and psychosocial burden of moderate to severe AD in Canadian children. Quality of life, access to care, and disease management are all areas of concern for patients and their families and warrant attention from individual clinicians and the health care system as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 4 publications
1
36
0
Order By: Relevance
“…The results of our and other [30][31] studies indicate a dynamic increase in the prevalence of AD. In our studies, we confirmed the recommendations [32] to grade the severity of AD, while agreeing that the best tool for assessing clinical signs of AD is the SCORAD scale.…”
Section: Discussionsupporting
confidence: 76%
“…The results of our and other [30][31] studies indicate a dynamic increase in the prevalence of AD. In our studies, we confirmed the recommendations [32] to grade the severity of AD, while agreeing that the best tool for assessing clinical signs of AD is the SCORAD scale.…”
Section: Discussionsupporting
confidence: 76%
“…Some sleep deprivation is expected for all parents of young infants, but childhood AD worsens this issue considerably. Sleep disruption is well known to occur in patients with AD, so it is unsurprising that their parents’ sleep is also diminished . The sleep loss in some parents of AD patients can be comparable in severity to that experienced by parents of children with various other chronic conditions, including autism spectrum disorder, mental retardation, and seizure disorders .…”
Section: Methodsmentioning
confidence: 99%
“…Sleep disruption is well known to occur in patients with AD, 2 so it is unsurprising that their parents' sleep is also diminished. 6 The sleep loss in some parents of AD patients can be comparable in severity to that experienced by parents of children with various other chronic conditions, including autism spectrum disorder, mental retardation, and seizure disorders. 23 In a survey study of parents of 203 infants attending pediatric dermatology clinics for AD, caregivers reported that the greatest impact that AD had on their own lives is sleep loss and tiredness.…”
Section: Parental Sleep Disturbancementioning
confidence: 98%
See 1 more Smart Citation
“…While mortality from skin disease is rare, many skin diseases are chronic and associated with substantial morbidity. [1][2][3][4] There are estimates of incidence and prevalence of specific diseases such as psoriasis, atopic dermatitis, and melanoma, but to date, there has been no comprehensive study of the burden of skin diseases and their associated disability in Canada. [5][6][7] The Global Burden of Disease (GBD) study aims to provide estimates of the fatal and nonfatal burden of disease.…”
Section: Introductionmentioning
confidence: 99%